Gambaran Penyesuaian Perkawinan Ditinjau dari Tingkat Pendidikan dan Kehadiran Anak di Bali - Ni Luh Prema Shantika Putri Laksmi; Ni Made Ari Wilani (Humanitas (Jurnal Psikologi), 2023)
Early life after marriage requires marital adjustments. The high number of divorce cases that occur in Bali and the rate of domestic violence are indications of poor marital adjustment. Level of education and the presence of children are factors that can influence marital adjustment. Researchers want to know the marital adjustment in Bali in terms of education level and presence of children. Quantitative research design with data analysis using different tests. The characteristics of the subjects in this study were individuals aged 20-30 years who were married, had a marriage 0-5 years, and lived in Bali. The scale used is the Dewi & Wilani (2016) Marital Adjustment Scale referring to the 4 aspects of marital adjustment from Spanier (1976). The data collection method was carried out incidentally which met the research criteria. Based on the 94 subjects who participated in this research, it was found that there was a significant difference in marital adjustment based on the level of education (F(3,90) =2.956; p= 0.037), and there was a significant difference based on the presence of children (p<0.05). The results of this research can add insight to early adults, the government, and future researchers